Decreasing marginal impatience in a monetary growth model - Ken-Ichi Hirose; Shinsuke Ikeda (Osaka University, Institute of Social and Economic Research (ISER), 2004)
Unlike the standard assumption that the degree of impatience, measured by the rate of time preference, is increasing in wealth, empirical studies support that impatience ismarginally decreasing. By introducing decreasing marginal impatience into the neoclassical monetary growth model á la Sidrauski, we show that (i) consistently with empirical results, an increase in the core rate of inflation reduces capital stocks in a steady state; and that (ii) its long-run welfare cost is larger than predicted with increasing or constant marginal impatience, implying that estimates of the inflation cost which have so far been obtained by assuming constant time preference may be underestimates.
Keywords: D90; E00; 330; decreasing marginal impatience; time preference; inflation; the Tobin effect; Monetäre Wachstumstheorie; Inflationsrate; Zeitpräferenz